Aplikasi Simulasi TOEFL ITP â€œTOEFL OS (Offline Simulation)â€ Berbasis Android - Rizkiyah, Umi; Sukamta, Sri; Purbawanto, Sugeng (Jurusan Teknik Elektro Universitas Negeri Semarang, 2017)
English is an international language that is needed in the development of global information technology. Each person's English skills can be measured by a test called TOEFL. TOEFL (Test of English as a Foreign Language) is a test oriented to American English. The English test used in the eucation world is the TOEFL ITP (Institutional Testing Program) because it focuses on a particular institution. Currently, there are many universities that use TOEFL ITP as one of the requirements of graduation that is adjusted to the standards of each university. Currently many agencies provide services to study and practice TOEFL at a cost that is quite expensive. In this study made alternative implementation of TOEFL simulation to learn, practice and perform TOEFL simulation through android smartphone. The results showed the validation and validation category of the media, the TOEFL ITP simulation application included in the category very well. The effectiveness test obtained Sig. (2-tailed) less than 0.05 ie 0.012 and 0.002 with average Sig. (2-tailed) is 0.007. Test results of 82.5% outcome result results with very good category. So it can be concluded that the application called TOEFL OS enthused by the user and has been appropriate user needs as an alternative learning media TOEFL.